Teknik Bedeng Permanen Alternatif Mengurangi Biaya Produksi Usahatani Pada Kondisi Pendemi Covid19 - I Nyoman Soemeinaboedhy; Padusung Padusung; I Gusti Made Kusnarta; Mahrup Mahrup; Fahrudin Fahrudin (Universitas Mataram, 2021)
Permanent raised-beds can be used in several soil seasons and aim to increase production through the application of sustainable and sustainable agriculture and can improve the welfare of farmers. The three basic principles of conservation agriculture are: i) applying minimal or no tillage ii) applying cover crops continuously throughout the year, and iii) applying crop diversification, either by intercropping, crop rotation, and consecutive cropping (relay cropping), especially between non-legume and legume crops. Service activities provide knowledge to farmers by demonstrating the application of permanent bed farming techniques to reduce farm production costs. This activity is expected to: 1) as an example of the application of permanent bed-based agriculture to prevent soil erosion by planting cover crops and mulch, 2) as an example of a permanent bed technique to maintain soil stability and save costs, 3) as an example of a natural way to restore physical, chemical and biological fertility of dry soil, and 4) as an example of how to increase soil productivity in dry paddy fields typology. To achieve this, several conservation methods will be introduced, as well as several types of vegetable crops and minimum tillage techniques will be introduced.